2020
DOI: 10.1155/2020/1767056
|View full text |Cite
|
Sign up to set email alerts
|

PART1 and hsa-miR-429-Mediated SHCBP1 Expression Is an Independent Predictor of Poor Prognosis in Glioma Patients

Abstract: Gliomas are the most common primary brain tumors. Because of their high degree of malignancy, patient survival rates are unsatisfactory. Therefore, exploring glioma biomarkers will play a key role in early diagnosis, guiding treatment, and monitoring the prognosis of gliomas. We found two lncRNAs, six miRNAs, and nine mRNAs that were differentially expressed by analyzing genomic data of glioma patients. The diagnostic value of mRNA expression levels in gliomas was determined by receiver operating characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…GSE108474 ( https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi ) contains 671 samples, which included 21 cases of non-tumor tissue, 2 WHO grade I gliomas, 99 WHO grade II gliomas, 84 WHO grade III gliomas, 134 grade WHO IV gliomas, and 331 without tissue grade ( Table 1 ). The WHO classification system was used according to our previous descriptions [ 6 , 20 ]. All data comes from public databases (GTEx, TCGA, GSE108474) and is completely anonymous.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GSE108474 ( https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi ) contains 671 samples, which included 21 cases of non-tumor tissue, 2 WHO grade I gliomas, 99 WHO grade II gliomas, 84 WHO grade III gliomas, 134 grade WHO IV gliomas, and 331 without tissue grade ( Table 1 ). The WHO classification system was used according to our previous descriptions [ 6 , 20 ]. All data comes from public databases (GTEx, TCGA, GSE108474) and is completely anonymous.…”
Section: Methodsmentioning
confidence: 99%
“…To explore the relationship between the risk model and common clinical traits, we analyzed the relationship between the risk model and these common clinical traits, such as ATRX status, Chr 19/20 co-gain, Chr 7 gain/Chr 10 loss, MGMT promoter status, 1P/19q co-deletion, IDH status, mutation count, histology, gender, grade, age and fustat (state of existence) [ 20 ]. We found that the risk model is related to all clinical traits except gender.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, PART1, as a novel lncRNA, has been associated with tumor progression, metastasis and chemotherapy resistance ( 22 , 23 ). In addition, PART1 has been found to be involved in the regulation of several signaling pathways, such as the PTEN/AKT signaling pathway ( 24 ), the microRNA (miR)-150-5p/LRG1 axis ( 22 ) and the miR-429/SHCBP1 regulatory network ( 25 ), suggesting that targeting PART1 may be a novel and promising therapeutic strategy in patients with cancer. Therefore, elucidation of the function of PART1 and its molecular mechanisms, may provide further understanding and enable treatment in a clinical setting for different types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Although much attempt has been focused on the glioma treatment, the 5 years survival rate is still unsatisfactory. 4 Ropivacaine, one of the safest local anesthetics, is widely used in cancer therapy. 5,6 Ropivacaine works via repressing the voltage-gated sodium channels.…”
Section: Introductionmentioning
confidence: 99%